Environmental Kuznets Curve: Economic Growth with Environmental Degradation In Indonesia - Prasetyanto, Panji Kusuma; Sari, Farmila (International Journal of Energy Economics and Policy, 2021)
Environmental Kuznets Curve (EKC) is a hypothesis of the influence of the relationship between environmental degradation and economic growth (GDP per capita) in the perspective of economic development. The purpose of this research is to prove that there is an economic growth influence on environmental degradation in the U-shaped EKC hypothesis and to determine the influence of primary energy consumption, income inequality, education level and Environmental degradation in the Sustainable development of Indonesia. The study used the Error Correction Model (ECM) Engel and Granger estimation techniques to determine the short-term and long-term impact of the 1994-2018 period in Indonesia. The results showed that the EKC was proven in the short term as well as in the long term. Economic growth variables and primary energy consumption have a positive and significant effect on environmental degradation. Income inequality is negatively influential but not significant in the short or long term, the level of education in the short term is insignificant but positive and significant in the long term. For the export variables in the short term, the effect is positive and significant but not with long term against environmental degradation. Keywords: Carbondioxide emissions, Environment Kuznets Curve, Error Correction Model, economic growth, Sustainable Development JEL Classifications: O44, Q56 DOI: https://doi.org/10.32479/ijeep.11609